Characteristics of Gamma-ray loud blazars in the VLBA Imaging and Polarimetry Survey - Linford, J; Taylor, G; Romani, R; Healey, SE; Helmboldt, J; Readhead, A; Reeves, R; Richards, J; Cotter, G (2011)
The radio properties of blazars detected by the Large Area Telescope (LAT) on board the Fermi Gamma-ray Space Telescope have been observed as part of the VLBA Imaging and Polarimetry Survey. This large, flux-limited sample of active galactic nuclei (AGNs) provides insights into the mechanism that produces strong γ-ray emission. At lower flux levels, radio flux density does not directly correlate with γ-ray flux. We find that the LAT-detected BL Lac objects tend to be similar to the non-LAT BL Lac objects, but that the LAT-detected FSRQs are often significantly different from the non-LAT FSRQs. The differences between the γ-ray loud and quiet FSRQs can be explained by Doppler boosting; these objects appear to require larger Doppler factors than those of the BL Lac objects. It is possible that the γ-ray loud FSRQs are fundamentally different from the γ-ray quiet FSRQs. Strong polarization at the base of the jet appears to be a signature for γ-ray loud AGNs. © 2011. The American Astronomical Society. All rights reserved. Printedin the U.S.A.